Further Evidence on the Determinants of Municipal Audit Fees - Ward, D. Dewey; Elder, Randal J.; Kattelus, Susan C. (The Accounting Review, 1994)
[In this study, we extend existing municipal audit fee models (e.g., Rubin 1988; Baber et al. 1987) by incorporating additional variables that reflect unique aspects of the municipal accounting and auditing environment. These variables relate to auditor expertise, audit adjustments, audit qualifications, and measures of agency costs related to the level of taxpayer funding of services. We test our model on a sample of Michigan municipalities and find that the fee model explains a greater portion of the variation in audit fees than previous studies. Palmrose (1986) did not find a significant relationship between audit fees for private sector companies and measures of auditor industry experience. In a study of auditors of Texas school districts, Deis and Giroux (1992a) find that audit quality is positively associated with the number of school districts audited by the audit firm. In our study, the regional audit firm with the largest number of municipal clients received significantly higher fees. This result is consistent with the existence of a fee premium due to brand-name reputation based on industry experience. Previous research has not documented reputation effects for non-Big 6 firms. We also find that audit fees are positively associated with the number of audit adjustments. Many of the governmental entities in our sample have significantly more audit adjustments than entities in the private sector (Kreutzfeldt and Wallace 1986; Hylas and Ashton 1982), suggesting that there is opportunity for improvement in many municipal accounting and control systems. The frequency and nature of audit adjustments in the public sector may be an area of future research interest. Previous studies of municipal audit fees (Baber et al. 1987; Rubin 1988; Copley 1989) have not found a significant relationship between audit qualifications and audit fees. We separate audit qualifications into two types of qualifications expected to have different relationships to audit fees. However, neither qualification variable is found to be significantly related to audit fees. The frequent nature of opinion qualifications in the municipal sector suggests that these qualifications may not involve significant amounts of additional audit effort. We find some evidence that audit fees are positively related to agency variables which measure the extent of taxpayer funding of services (Copley 1991; Deis and Giroux 1992b). These variables may capture elected officials' incentives to demonstrate accountability to taxpayers. We do not find a relationship between audit fees and measures of agency costs related to the form of government. We also do not find a relationship between audit fees and measures of political competition. Future research should consider a broader set of incentives for monitoring in the public sector, including agency costs which measure taxpayer funding of services.]